Hyolith-dominated shell beds from the Lampazar Formation in NW Argentina: patterns and processes of origin in the Late Cambrian (Furongian) seas of western Gondwana - Simões, Marcello Guimarães [UNESP]; Acenolaza, Guillermo F.; Laurie, JR; Brock, G. A.; Paterson, JR (Assoc Australasian Palaeontologists, 2009)
Late Cambrian (Furongian) shell beds in the Salta Province of NW Argentina are unique because of the presence of abundant hyolith skeletal remains within them. Hyolith shell beds are located in the mid-upper part of the Lampazar Formation at the Angosto de La Quesera locality, and are the first recorded accumulations of this type in the lower Palaeozoic of the South American Andean Basin. The shell beds are of the order of several mm thick, and are laterally persistent within outcrop scale, with a few metres of lateral development. Two types of hyolith shell beds are recognised: Type 1 is a storm-dominated, event concentration, represented by dispersed to densely packed accumulations of well preserved hyolith and gastropod shells (Strepsodiscus austrinus). Hyolith conchs are current oriented with the long axes parallel to unidirectional flow on the sandstones surfaces. Type 2 shell beds are background, composite concentrations, of poorly preserved, comminuted debris of hyolith shells with associated gastropod and trilobite sclerites (dominated by Parabolina, Beltella and Leiostegium). The genesis of both shell beds was controlled primarily by physical processes, such as storms and current and/or wave agitation. The thickness, simple internal fabric and geometry shown by both accumulations are typical of Cambrian-style shell-beds.
Keywords: Hyoliths; shell beds; biostratinomy; Cambrian; Furongian; Argentina